Performance Test for the SIGMA Communication System - Seonyeong Jeong; Hyojeong Lee; Seongwhan Lee; Jehyuck Shin; Jungkyu Lee; Ho Jin (Journal of Astronomy and Space Sciences, 2016)
Scientific CubeSat with Instruments for Global Magnetic Fields and Radiations (SIGMA) is a 3-U size CubeSat that will be operated in low earth orbit (LEO). The SIGMA communication system uses a very high frequency (VHF) band for uplink and an ultra high frequency (UHF) band for downlink. Both frequencies belong to an amateur band. The ground station that communicates with SIGMA is located at Kyung Hee Astronomical Observatory (KHAO). For reliable communication, we carried out a laboratory (LAB) test and far-field tests between the CubeSat and a ground station. In the field test, we considered test parameters such as attenuation, antenna deployment, CubeSat body attitude, and Doppler frequency shift in transmitting commands and receiving data. In this paper, we present a communication performance test of SIGMA, a link budget analysis, and a field test process. We also compare the link budget with the field test results of transmitting commands and receiving data.